Walter Scheidel (ed.). The Science of Roman History: Biology, Climate, and the Future of the Past. - Russell, Ben (Journal of Greek Archaeology, 2019)
Human history and natural history are intrinsically connected and new scientific advances are increasingly re-shaping our understanding of the Roman environment, which has significant implications for Roman historians. This is the premise laid out in the introduction of this volume. Despite its title, it does not seek to explore all of the numerous and varied ways in which scientific approaches have informed scholarship on antiquity; there is no discussion of new archaeometric techniques now applied to archaeological materials as standard, or indeed of remote sensing or dating techniques. Climate and biology, as the sub-title explains, are the focus here. The broader aim is to test the fertility of the intersection between archaeo-historical research on the one hand and natural-scientific studies on the other.